Analysis of Cervical Cancer Screening at Patan Hospital Nepal - RC, Laxmi; Shrestha, Prashanti; Pradhan, Binita (Journal of Chitwan Medical College, 2018)
Background: Cervical cancer is among the most common cancer in women of Nepal. This disease undergoes a state of prolong premalignant state during which it can be detected and treated effectively. Papanicolaou (pap) smear is an effective method of identifying premalignant disease and with this there has been more than 90 percent decrease in the incidence of cervical cancer. The objective of this study was to analyse the pattern of Pap smear screening at Patan hospital. Methods: This is a population based retrospective cross-sectional study conducted at Patan hospital, Lagankhel. The study population includes women with gynaecological symptoms who required Pap smear screening over a period of two years. The pap smear data were collected and statistical analysis was done. Results: Among 1993 smear studied, only 89 reports had some form of intraepithelial lesion. The most prevalent lesion was low grade intraepithelial lesion (49.43%) whereas the least common was Atypical glandular cells (1.12%). The highest number of respondent were in the age of 30 – 40 years whereas the lowest was in the group of age less than 20 years. The patient who had abnormal epithelial lesions had multiple symptoms like vaginal discharge, vulval itching and lower abdominal pain. Conclusions: Pap smear screening should be started by the age of 21 and should be done in all women with any gynaecological symptoms.